Identification and validation of PSMB7 as a novel biomarker for prognosis and immune infiltrates of lung adenocarcinoma - Chen,Yan; Ran,Xin; Fu,Ping; Ao,Jie; Zhu,Guihua; Zhao,Lianhua; Xiao,HuaLiang (PeerJ, 2025)
Background Lung adenocarcinoma (LUAD) is one of the most prevalent types of lung cancer globally; it is characterized by high incidence and mortality rates and contributes to over 1.8 million deaths annually. PSMB7, a crucial component of the 20S proteasome involved in protein degradation and antigen presentation, has been implicated in various cancers; however, its specific function in LUAD remains inadequately explored. Methods This research aimed to investigate the expression of PSMB7 in LUAD and its clinical significance using real-time quantitative PCR, immunohistochemistry, differential expression analysis, pathway enrichment analysis, immune cell infiltration, and DNA methylation. Results PSMB7 expression levels in LUAD tissues were considerably higher than those in the surrounding normal lung tissues and were associated with advanced pathological stages and poorer clinical outcomes. High PSMB7 expression was correlated with reduced overall and disease-specific survival. Functional enrichment analysis indicated that the differentially expressed genes associated with PSMB7 were mainly involved in protein–DNA complex assembly and chromatin remodeling. Moreover, LUAD tissues showed lower DNA methylation in PSMB7 promoters than that in normal lung tissues, which was correlated with reduced survival rates. A negative correlation was observed between PSMB7 levels and immune cell infiltration, particularly for effector memory T, B, follicular helper T, and mast cells. Conclusions We identified PSMB7 as a promising biomarker for LUAD prognosis because of its strong association with tumor progression and immune microenvironment modulation. Future studies should explore therapeutic strategies targeting PSMB7 to improve patient outcomes for LUAD.
Keywords: Lung adenocarcinoma; PSMB7; Biomarker; Prognosis; Immune microenvironment